Navī kavitā : madhyama kadanāṃ payāsa kāvyo - Jhaveri, Mansukhlal Maganlal, 1907-; Vakīla, Ramaṇalāla Naraharilāla, 1908- (SAMP early 20th-century Indian books project ;, 1952)
Anthology of modern Gujarati poetry.